Identification of the Oscillation Period of Chemical Reactors by Chaotic Sampling of the Conversion Degree - Lawnik Marcin; Berezowski Marek (Chemical and Process Engineering)
To stabilise the periodic operation of a chemical reactor the oscillation period should be determined precisely in real time. The method discussed in the paper is based on adaptive sampling of the state variable with the use of chaotic mapping to itself. It enables precise determination of the oscillation period in real time and could be used for a proper control system, that can successfully control the process of chemical reaction and maintain the oscillation period at a set level. The method was applied to a tank reactor and tubular reactor with recycle.